2016
DOI: 10.1182/blood-2016-03-705319
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease monitoring and immune profiling in multiple myeloma in elderly patients

Abstract: Key Points• MRD monitoring is one of the most relevant prognostic factors in elderly MM patients, irrespective of age or cytogenetic risk.• Second-generation MFC immune profiling concomitant to MRD monitoring also helped to identify patients with different outcomes.The value of minimal residual disease (MRD) in multiple myeloma (MM) has been more frequently investigated in transplant-eligible patients than in elderly patients. Because an optimal balance between treatment efficacy and toxicity is of utmost impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 35 publications
5
124
0
1
Order By: Relevance
“…In recent years, reaching minimal residual disease (MRD) negativity has also become an important treatment milestone in MM, as studies have repeatedly demonstrated positive prognostic outcomes in patients who are MRD negative [57][58][59]. The PETHEMA/ GEM group has also published two recent publications showing better survival outcomes in MRD negative high-risk patients than those who were MRD positive [60,61].…”
Section: Goals Of Treatmentmentioning
confidence: 97%
“…In recent years, reaching minimal residual disease (MRD) negativity has also become an important treatment milestone in MM, as studies have repeatedly demonstrated positive prognostic outcomes in patients who are MRD negative [57][58][59]. The PETHEMA/ GEM group has also published two recent publications showing better survival outcomes in MRD negative high-risk patients than those who were MRD positive [60,61].…”
Section: Goals Of Treatmentmentioning
confidence: 97%
“…We (submitted] and others 120 have clearly established that the more events that are acquired, the more sensitive the assay becomes, and the higher the predictive value for PFS. In most clinical laboratories, the detection sensitivity of MFC to identify neoplastic PCs in the bone marrow ranges from 10 −4 (1 in 10,000 cells) to 10 −5 (1 in 100,000 cells).…”
Section: Minimal Residual Disease Testingmentioning
confidence: 84%
“…55,115118 Due to the long latency between drug development and the approval to be considered as therapeutic options, the measurement of MRD by MFC as an independent method to predict PFS and OS for patients diagnosed with PCD has been employed. 119,120 All flow cytometric studies to date have strongly correlated the measurement of MRD with PFS and OS at the Day 100 time point, reducing from years to months the time required to reach meaningful clinical outcomes. 121124 …”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, by using 8-color flow cytometry to simultaneously assess MRD and characterize patients’ immune profile, we were able to show that a few MRD positive cases - those showing a strong recovery of the normal B-cell lymphopoiesis - have similar outcomes to those of MRD negative patients. 23 This suggests that despite MRD positivity, the intact immune surveillance was profitable in these patients. Finally, we have observed that MM patients attaining long-term survival (i.e., progression-free survival [PFS] for more than 10 years) showed a unique immune profile with a higher number of effector cells (T cells, NK cells, DCs, normal PCs), and a lower number of Tregs, underlying the importance of an active immune system to control disease evolution.…”
Section: Impaired Immune Surveillance In MMmentioning
confidence: 96%